(untitled) (Proceedings of the North American Academy of Liturgy, 2025)
This article explores some of the complexities of celebrating the eucharist as a sign of reconciliation. In particular, this article focuses on the context of Indigenous-Settler reconciliation in Canada. This context is explored through a visual ethnographic study of two papal rituals during Pope Francis' 2022 penitential visit to Canada. These two rituals are analyzed using the stages of social drama developed by Victor Turner and further developed by Kimberly Belcher. From this analysis, the article demonstrates how the eucharist can inadvertently conflate the unity of the participants with an imposed uniformity. This discussion draws upon the work of Lauren Winner and Susan Reynolds. As a way of conclusion, the article points towards lived solidarity as a potential remedy for the imposition of uniformity.